Learning culture of Iranian and Chinese-Malaysian undergraduate students - Omidvar, Pegah; Chan, Mei Yuit; Yap, Ngee Thai; Bolong, Jusang (Universiti Putra Malaysia Press, 2012)
With the increasingly multicultural and multi-national demographics of students in the classroom, teachers find themselves having to face the challenges of teaching students from diverse cultural backgrounds. While much research has been done on individual differences in learning attitudes, learning strategies and learning styles, there is a severe lack of work done to investigate whether differences in the attitudes and values towards learning could be attributed to group differences. This paper reports the findings of a study on the differences in learning culture between Iranian and Chinese-Malaysian students. A questionnaire that measures learning culture was developed using Hofstede’s (1980) cultural dimensions. The questionnaire consists of 24 items covering four dimensions, namely, collectivism/individualism, power distance, uncertainty avoidance, and masculinity/femininity. One hundred and fifty Iranian and the same number of Chinese-Malaysian undergraduate students participated in the study. The results showed that there is a significant difference in the collectivism/individualism, uncertainty avoidance, and masculinity/femininity dimensions between these two groups of students. Implications of the results to the teaching and learning of second/foreign language are discussed.